Mindfulness in the classroom : strategies for promoting concentration, compassion, and calm - Armstrong, Thomas (ASCD, 2019)
Thomas Armstrong integrates brain research with simple, authentic practices to show how mindfulness can lower stress and increase positive experiences for teachers and students.